On Generalized Distinguished Prime Submodules: S. Ebrahimi Atani, F. Esmaeili Khalil Saraei - Team, Support (Thai Journal of Mathematics, 2008)
Distinguished prime submodules of a module over a commutative ring with non-zero identity have been investigated in [1]. Here we study generalized distinguished prime submodules of modules and we will give a condition which allow us to determine whether the radical of submodules of a module are a generalized distinguished prime submodule.